Measuring technical efficiency of wireless and wired technologies in Nigeria cyber cafés - Sule Magaji; Chukwuemeka I. Eke (CBN Journal of Applied Statistics, 2013)
This study examined the technical efficiency (TE) of two different remote internet access methods, wireless and wired in Nigeria using the stochastic frontier production function analysis. Primary data were obtained through the use of a set of questionnaire from four hundred and fifty representative samples of cyber café operators. The results show that in Nigeria, in spite of the acclaimed superiority of wireless technologies internationally, wired technology (within the context of Nigeria's socio-economic constraints) is (still) more efficient technically with mean technical efficient indices of 0.914 and 0.797 respectively. The analysis also suggests that age and years of education of cyber café operators have positive significant influence on the level of technical efficiency. The policy implication of the findings in this study is that there is scope for raising the present level of TE of production in the study area. More so, since age and education variables have direct relationship with the level of TE therefore, policies should encourage more of the younger and better educated potential operators to go into the enterprise.
Keywords: O3; 330; Cyber Café wireless; Efficiency Measurement; Stochastic Frontier Production